134k views
5 votes
Solve for c.

Solve for x.

Solve for c.

Solve for x.

Solve for x.

Solve for c. Solve for x. Solve for c. Solve for x. Solve for x.-example-1
Solve for c. Solve for x. Solve for c. Solve for x. Solve for x.-example-1
Solve for c. Solve for x. Solve for c. Solve for x. Solve for x.-example-2
Solve for c. Solve for x. Solve for c. Solve for x. Solve for x.-example-3
Solve for c. Solve for x. Solve for c. Solve for x. Solve for x.-example-4
Solve for c. Solve for x. Solve for c. Solve for x. Solve for x.-example-5
User Cantillon
by
6.7k points

2 Answers

3 votes

Answer:

1) c = 9 - a + b

2) x=-2 or x=3

3) c = 9 - a + b

4) X= 11/3

5) x=-2 or x=3

User Toshiro
by
5.8k points
5 votes

Answer:

1) The option
c=9-a+b is correct.

2) The option x=-2 or x=-3 is correct.

3) The option
c=9-a+b is correct.

4) The option
x=(11)/(3) is correct.

5) The option x=-2 or x=-3 is correct.

Explanation:

1) Given equation is
√(a-b+c)=3

Now to solve the equation for c:


√(a-b+c)=3

Squaring on both sides we get


(√(a-b+c))^2=3^2


a-b+c=9


c=9-a+b

Therefore the option
c=9-a+b is correct.

2) Given equation is
√(3x+10)=x+4

Now to solve the equation for x:


√(3x+10)=x+4

Squaring on both sides we get


(√(3x+10))^2=(x+4)^2


3x+10=x^2+8x+16


x^2+8x+16-3x-10=0


x^2+5x+6=0 which is a quadratic equation in x.

We can solve it by finding factors


x^2+5x+6=(x+2)(x+3)


(x+2)(x+3)=0

x+2=0 or x+3=0

Therefore x=-2 or x=-3

Therefore the option x=-2 or x=-3 is correct.

3) Given equation is
√(a-b+c)=3

Now to solve the equation for c:


√(a-b+c)=3

Squaring on both sides we get


(√(a-b+c))^2=3^2


a-b+c=9


c=9-a+b

Therefore the option
c=9-a+b is correct.

4) Given equation is
√(x+3)=2√(x-2)

Now to solve the equation for x:


√(x+3)=2√(x-2)

Squaring on both sides we get


(√(x+3))^2=(2√(x-2))^2


x+3=2^2(x-2)


x+3=4(x-2)


x+3=4x-8


4x-8-x-3=0


3x-11=0


x=(11)/(3)

Therefore the option
x=(11)/(3) is correct.

5) Given equation is
√(3x+10)=x+4

Now to solve the equation for x:


√(3x+10)=x+4

Squaring on both sides we get


(√(3x+10))^2=(x+4)^2


3x+10=x^2+8x+16


x^2+8x+16-3x-10=0


x^2+5x+6=0 which is a quadratic equation in x.

We can solve it by finding factors


x^2+5x+6=(x+2)(x+3)


(x+2)(x+3)=0

x+2=0 or x+3=0

Therefore x=-2 or x=-3

Therefore the option x=-2 or x=-3 is correct.

User Fluminis
by
5.4k points